Trans-European adaptations in the diamond way: negotiating public opinions on homosexuality in Russia and in the U.K. - Scherer, Burkhard (Online - Heidelberg journal of religions on the internet, 2014)
This paper focuses on a Neo-Orthodox Tibetan Buddhist movement’s shifting trans-European positioning on the web and in its media self-representation with regard to public discourses around homosexuality. The analysis presented also proves methodologically relevant, exemplifying through reflexive ethnography how outsider/insider scholars can manoeuvre religious politics.As a global movement of the Karma Kagyu school of Tibetan Buddhism, the Diamond Way of the Danish lay teacher Ole Nydahl has been particularly successful in its proselytising efforts throughout Eastern and Central Europe. Previous research has noted the selectively socially conservative and mildly homophobic tendencies of the Diamond Way (Scherer 2011; 2013). In the trans-European context, from Russia to the U.K., Nydahls and the movement’s mild homophobia/strained LGBT-neutrality appears to draw public criticism for either being too pro-LGBT or too anti-LGBT. The investigation highlights the shifting public perceptions and socio-religious political frontlines in Russia and the U.K. and reveals a pattern of opportunism and (non-)negotiating public opinions.